Correlation of Neutrophil Lymphocyte Ration (NLR) Values with Severe Preeclampsia, HELLP Syndrome and Eclampsia - Lisfi, Indah; Sriyanti, Roza; FIrdawati, Firdawati (Fakultas Kedokteran Universitas Andalas, 2023)
Background: Preeclampsia (PE) is the leading cause of maternal and fetal morbidity and mortality. The disease is characterized by hypertension (≥140/90 mmHg), proteinuria, thrombocytopenia, renal failure, neurological complications, liver involvement, and fetal growth retardation. HELLP syndrome is a variant of preeclampsia that causes an increase in liver enzymes and a low platelet count. Eclampsia is the heaviest complication of preeclampsia. Neutrophil lymphocyte ratio (NLR) is part of the leukocyte type count examination which is an easy, available examination parameter and can be used as an index of the severity of systemic inflammation. This study aimed to determine the relationship of neutrophil-lymphocyte ratio (NLR) values with severe Preeclampsia, HELLP syndrome, and eclampsia. Method: This research is a comparative analytical study with a case control study approach. This research was conducted from April-November 2022. This study was conducted at the emergency room (ER) and inpatient department of Obstetrics and Gynecology, Faculty of Medicine, Universitas Andalas – RSUP Dr. M. Djamil Padang. The study sample was part of the population that met the inclusion and exclusion criteria. The study required 108 samples, namely 27 from the severe preeclampsia group, 27 from the eclampsia group, 27 from the HELLP syndrome group, and 27 from the control group. Bivariate statistical analysis using Independent T-Test. Samples were taken by the method of consecutive sampling. The data were analyzed at a 95% confidence interval, if obtained p value<0.05 then there is a significant relationship. The Data was analyzed by the SPSS computer program. Results: The results of this study obtained neutrophil-lymphocyte ratio in eclampsia has the highest average value compared with HELLP syndrome, severe preeclampsia, and control. While HELLP syndrome has a higher mean value than severe preeclampsia and control and subsequently severe preeclampsia also has a higher mean value NLR than control. This study found a significant relationship between neutrophil-lymphocyte ratio (NLR) with severe Preeclampsia, HELLP syndrome, and eclampsia (all p values=0.000). Conclusion: This study proves that neutrophil-lymphocyte ratio (NLR) has a significant relationship with severe Preeclampsia, HELLP syndrome, and eclampsia so further research can develop this study by analyzing other factors that affect preeclampsia. For clinicians can make this study as a reference in monitoring the progression of inflammation that occurs in severe preeclampsia, HELLP syndrome, and eclampsia.